HAMBATAN BEKERJA DAN BERAKTIVITAS PADA PEREMPUAN JAWA KELAS MENENGAH - Arundati Shinta (Jurnal Psikologi, 2007)
Six Javanese women participated on this qualitative study in order to understand their obstacles to engage on a job outside of their homes. They had college to university educational level, middle to high class, engaged on a job before married. After married till recently they were unemployed although they had trivial fertility problems. There were various reasons for their unemployed status such as husband had not given any permission to work, husband's jealous, wife’s primary responsibility was to accomplish the unending domestic casks not to work, providing a good service for husband and children, and wife’s low self-efficacy Indeed, this unemployment was heartbreaking since wife’s high potentiality could not be manifested because of husband's sex typed attitude. Unfortunately this powerless self-perception was also agreed by those wives. Those wives were more likely to be lazy or could not think visionary to train their skills, because their family economy situation had not demanded them to work. Those high class wives should learn more from the lower class Javanese wives who had been able to be more egalitarian toward their husbands. It was because they had to work, otherwise their children would be starved. Those rich wives should feel embarrassment that their high educational level had been related to the sex-typed attitude and more subordinate position.